2014
DOI: 10.1021/jf405591g
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Decreases the Micellar Solubility of Cholesterol via Specific Interaction with Phosphatidylcholine

Abstract: The mechanisms underlying the effect of epigallocatechin gallate (EGCG) on the micellar solubility of cholesterol were examined. EGCG eliminated both cholesterol and phosphatidylcholine (PC) from bile salt micelles in a dose-dependent manner in vitro. When the bile salt micelles contained a phospholipid other than PC, neither cholesterol nor the phospholipid was eliminated following the addition of EGCG. When vesicles comprised of various phospholipids were prepared and, EGCG was added to the vesicles, EGCG ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 36 publications
7
41
1
3
Order By: Relevance
“…Similar decreases in total plasma cholesterol have been reported for proanthocyanidins isolated from the seed shells of Japanese horse chestnut [24] and black tea [3] and may be attributed to a decrease in the micellar solubility of cholesterol, as has been previously shown in a study using Reishi extracts [28]. In turn, the decrease in micellar solubility may result from specific interactions between proanthocyanidins and phosphatidylcholine, as was reported for epigallocatechin gallate [29].…”
Section: Effects Of Srpas On Serum and Liver Lipid Peroxides In Mice supporting
confidence: 76%
“…Similar decreases in total plasma cholesterol have been reported for proanthocyanidins isolated from the seed shells of Japanese horse chestnut [24] and black tea [3] and may be attributed to a decrease in the micellar solubility of cholesterol, as has been previously shown in a study using Reishi extracts [28]. In turn, the decrease in micellar solubility may result from specific interactions between proanthocyanidins and phosphatidylcholine, as was reported for epigallocatechin gallate [29].…”
Section: Effects Of Srpas On Serum and Liver Lipid Peroxides In Mice supporting
confidence: 76%
“…Kobayashi et al suggested that EGCG has an inhibitory effect on cholesterol absorption in the intestine through its action on micelles [5]. Suzuki et al compared the effects of Benifuuki extracts that contain methylated catechins such as EGCG3”Me with those of Yabukita extracts in animal studies of mice fed a high-fat/high-sucrose diet.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG is the most prevalent catechin in green tea and it decreases the micellar solubility of cholesterol via specific interaction with phosphatidylcholine [5,6]. Previous studies have found that continuous intake of green tea containing catechins and caffeine (five or more cups per day) may be beneficial for body weight management, vascular disease risk reduction via LDL-cholesterol improvement, and type 2 diabetes risk reduction through the lowering of fasting blood glucose levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…2B). While EGCG is an established HATi and could affect foam cell formation by regulating the expression of scavenger receptors and efflux proteins, EGCG also influences micellar cholesterol solubility [16] and could in this way also alter foam cell formation. In an attempt to explain the observed effects on oxLDL uptake, we measured the expression of Cd36 and Msr1 as oxLDL uptake mediators and Abca1 and Abcg1 as cholesterol efflux regulators.…”
Section: Hdac Inhibition Enhances Histone Acetylation and Expression mentioning
confidence: 99%